Analysis of Pesticide Usage Behavior and Personal Protective Equipment (PPE) among Farmers in Batu Bangka Village - Rafi’ah; Harmili; Asri Reni Handayani; Iga Maliga; Ana Lestari (Jurnal Ilmiah Kesehatan)
Various chronic health effects can arise due to long-term exposure to pesticides. Unsafe pesticide usage behaviour and inadequate Personal Protective Equipment (PPE) usage pose potential hazards to farmers. This study aims to analyse the behaviour of pesticide usage and Personal Protective Equipment (PPE) among farmers in the Batu Bangka Village, West Nusa Tenggara. This research is a quantitative study using a cross-sectional approach. The study sample was taken using a simple random sampling technique, involving 40 individuals. Respondent characteristics indicate that respondents in the age category are predominantly between 36 and 45 years old, with 15 respondents (50%); those with elementary or junior high school education were 25 respondents (62.5%); and the majority have been farmers for more than 10 years (37.5%). Farmer behaviour and personal protective equipment show that many respondents have an inadequate knowledge level, with 27 respondents (67.5%); the majority have a good attitude, with 29 respondents (72.5%); and the majority have good practices, with 33 respondents (82.5%), but the majority do not use complete PPE, with 21 respondents (52.5%). Efforts and cooperation from various parties are needed to improve farmers' knowledge and advise farmers to use complete PPE to prevent pesticide poisoning and work-related diseases.